Not evolved to save the planet, yet capable to promote pro-environmental action leveraging human nature - Varella, Marco Antonio Correa; Novaes, Felipe Carvalho; Silva, Ramon Felipe Bicudo da; Romero, Renato de Mei; Gonçalves, Paulo Henrique Santos; Moura, Joelson Moreno Brito de; Silva, Risoneide Henriques da; Coelho, Matheus Adriano Ferreira; Costa, João Vitor Rodrigues; Silva Júnior, Mauro Dias; Rantala, Markus J.; Vuorinen, Katariina Elsa Maria (Frontiers in Psychology, 2025)
Anthropogenic environmental issues, from global warming to pollution, biodiversity loss, and natural resources depletion, require immediate action. Yet, inaction remains pervasive, and pro-environmental psychological interventions have, at best, yielded modest, short-lived effects. In this article, we argue that the development of more effective interventions could be aided by more nuanced discussion around two pervasive misguided assumptions: That human nature is inherently environmentally friendly, thus naturally inclined toward sustainability unless distorted by modern socioeconomic systems; on the other hand, that human nature is inherently destructive, posing a fundamental barrier to environmental action. We critically examine these presuppositions, their foundations, as well as their pro- and counterarguments, and argue that both are oversimplifications which overlook the current understanding on biological, evolutionary and behavioral sciences, disregarding its contextual nature. Many native populations have overexploited their resources, yet modern evolutionary psychology does not support the notion that human nature would be inherently unfit for environmental action. Evolved behavioral tendencies interact with socioeconomic environments which can lead to the relational properties of environmental destruction as well as to protection. Their high behavioral variability, interactivity, calibration, flexibility, plasticity, and co-optability enable a wide range of sustainable actions. Rather than seeing biological and evolutionary aspects as inherently pessimistic or optimistic per se, we call for more research which appropriately integrates behavioral biology and evolutionary psychology so that we can avoid the above-described erroneous presuppositions as well as related Moralistic and Naturalistic Fallacies. We also argue toward a more nuanced understanding of human nature, and thus design more effective interventions which fit our biological predispositions. Furthermore, promoting education, ethical control and responsible journalism may help to avoid fostering these misguided assumptions about human nature. We conclude that evolved, universal psychological tendencies neither justify inaction nor make sustainability unattainable. Instead, correctly understanding human nature serves as a crucial foundation for guiding us toward designing effective and lasting sustainable practices.